2010
DOI: 10.1159/000313874
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pregnancy, Hypertension and Nitric Oxide Inhibition on Rat Uterine Artery Myogenic Reactivity

Abstract: Background/Aims: The purpose of this study was to examine the effects of hypertension and nitric oxide (NO) inhibition on myogenic tone in uterine arteries during pregnancy. Methods: Premyometrial radial uterine arteries from nonpregnant and late pregnant Sprague-Dawley rats were evaluated for myogenic reactivity from the following groups: control, hypertensive/NO-inhibited (L-NAME treatment) and normotensive/NO-inhibited (L-NAME plus hydralazine). Results: In both nonpregnant and pregnant animals, L-NAME trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 83 publications
(56 reference statements)
2
23
0
Order By: Relevance
“…6,24 A recent study showed that L-NAME significantly increased myogenic tone. 22 We found that inhibition of eNOS with L-NAME enhanced the NaHS-induced reduction of the myogenic response, indicating an interaction between H2S and NO and that this interaction may generate nitrosothiol, which exhibits little or no vasorelaxant activity. 10, 34 The NO-induced vasorelaxation is mainly mediated by the cGMP pathway, but not the cAMP pathway.…”
Section: Discussionmentioning
confidence: 72%
“…6,24 A recent study showed that L-NAME significantly increased myogenic tone. 22 We found that inhibition of eNOS with L-NAME enhanced the NaHS-induced reduction of the myogenic response, indicating an interaction between H2S and NO and that this interaction may generate nitrosothiol, which exhibits little or no vasorelaxant activity. 10, 34 The NO-induced vasorelaxation is mainly mediated by the cGMP pathway, but not the cAMP pathway.…”
Section: Discussionmentioning
confidence: 72%
“…High-quality nursing to puerpera with pregnancy hypertension mainly focuses on psychological nursing, ward environment nursing, disease observation, nursing for preeclampsia and eclampsia, and post-delivery nursing [8,9]. This type of care provides comprehensive, systematic, and thorough nursing services to puerpera, thus improving outcomes of puerpera and newborns [10].…”
Section: Discussionmentioning
confidence: 99%
“…This was proofed by inhibition of NO will increased blood pressure of uterine arteries [16]. NO was produced by eNOS and iNOS.…”
Section: Placental Proreninmentioning
confidence: 92%